Pengaruh Struktur Aktiva, Likuiditas dan Profitabilitas Terhadap Struktur Modal pada Perusahaan Sub Sektor Industri Ritel yang Terdaftar di (BEI) Periode 2020-2022 - Selviana, Sella Maya; Prapanca, Detak; Sari, Herlinda Maya Kumala (Efektor, 2024)
This research was conducted on retail sub-sector industrial companies on the Indonesia Stock Exchange (BEI) with the title The Influence of Asset Structure, Liquidity and Profitability on Capital Structure in Retail Industrial Sub-Sector Companies Listed on (BEI) for the 2020-2022 Period. This research uses quantitative data with secondary data sources. This research uses a purposive sampling method. The data sample in this research is 33 samples of retail industry manufacturing companies from the 2020-2022 period. This research uses multiple linear analysis techniques, partially this research states that 1) asset structure partially has a positive and significant effect on capital structure, 2) partial liquidity has a negative and insignificant effect on capital structure, 3) profitability partially has an insignificant effect on capital structure, 4) asset structure, liquidity, profitability together (simultaneously) have a positive and significant effect on capital structure.